Waste Management In Construction Site - Chua, Mei King (2013)
Nowadays, the topic of environment friendly is popular in the construction industry in Malaysia. The control of wastes is one of the ways to achieve the eco-friendly status in the construction industry. An improper and failure in the implementation of construction waste management will cause higher costs and effect to our safety and health. Construction sector is playing a vital role in every developing country. Waste in the construction industry has been the subject of several research projects around the world in recent years. Some of them has been the subject of several research projects around the world in the recent years. Some of them have focused on the environment damage those results from the generation of material waste. Wyatt (1978) stressed the consequences of high level of waste in both reducing the future availability of material and energy, and creating unnecessary demands on the transportation system. The overconsumption and inefficiency used of materials was caused the presence of the waste getting worse. Waste was caused a lot of problems to the human. This dissertation aimed to identify the current issue of waste management in Malaysia and determine how the construction waste had been managed in order to propose a proper method in managing the construction waste to reduce the waste in construction site. The research methodologies used were desk study and questionnaire research. The experience contractors targeted and invited to complete a survey on how the construction had been managed for a project. This research is in assist the construction player in improving the waste management in term of construction materials.